Pengaruh Religiusitas terhadap Brand Loyality dan Keputusan Pembelian pada Hijab Zoya di Kota Malang(studi pada Pengunjung Butik Zoya di Mall Olympic Garden Malang) - Aisyah, Siti Aisyah; Faizin, Moh. Asroul Faizin (Journal of Economic, Management and Entrepreneurship, 2024)
PT Zoya is a fashion brand that pioneered the hijab and Muslim clothing that was founded in 2005, and already has more than 160 stores spread throughout Indonesia. In the current era, companies are required to compete competitively and move quickly in the face of competition. This study aims to determine and measure the effect of religiosity on brand loyalty and purchasing decisions on Zoya hijab in Malang. This research was conducted on visitors to Zoya's boutique at Mall Olympic Garden Malang. The selection of research samples using the Accidental Sampling method, the number of samples in this study was 100 respondents. The analysis used is PLS analysis using SmartPLS 3.0. The results of the study show that religiosity has a significant effect on Brand Loyalty, with a path coefficient value of 0.184 with a t-statistic value of 0.051, religiosity on purchasing decisions has a significant effect with a path coefficient value of 0.405 and a path coefficient value of 0.405. t-statistic of 3.317. And Brand Loyalty on Purchase Decisions has a significant effect with a path coefficient value of 0.309 and a t-statistic value of 2.645.